Regional inclusive development: An assessment of Russian regions - Rytova, E.; Gutman, S.; Sousa, C. (Sustainability, 2021)
The concept of inclusive development is gaining momentum in both the academic and policy-making arenas. There are a plethora of definitions and several indicators with which to monitor its progress at the national level. However, the regional level has been relatively overlooked in the analyses carried out by academics. This is particularly serious for large countries marked by deep regional disparities. The aim of this paper is to address this gap by proposing and applying a framework to assess inclusive development at the regional level. Drawing on a critical analysis of the concept and existing indexes, the paper proposes an index of Regional Inclusive Development and applies it to the regions of the Russian Federation. Moreover, it compares the suggested index with established indicators of regional socio-economic development, namely quality of life and gross product. The results support the idea that at the regional level, there is a significant correlation and interdependence between all dimensions of the sustainable development concept—environment, the economy, and society—and that inclusiveness should not be ignored or undervalued in the analysis of development processes. Furthermore, the results show significant differences in the positioning of the regions in terms of the inclusive development rankings as compared to their positions in the quality of life and gross product rankings. The results also reveal small interregional differences among Russian regions, which are unexpected given the size of the country.